Distance educational technologies in teaching mathematical disciplines to students of pedagogical universities - Nadezhda A. Khramova; Zhanna A. Sarvanova; Irina V. Kochetova; Natalia N. Derbedeneva (Revista on line de Política e Gestão Educacional)
The global pandemic of 2020 and 2021 was a turning point for the higher education system. Higher educational institutions should be ready to switch to a distance learning format at any time. This article attempts to discuss the problems that arise in teaching mathematics to students of a pedagogical university when introducing distance educational technologies and recommendations for solving these problems. To that end, a survey was performed conducted at the Faculty of Physics and Mathematics of the Mordovian State Pedagogical University. The research process comprises theoretical methods (studying and analyzing scientific, methodological, and educational literature). As a result, the analysis of modern distance educational technologies for students ' communication with a teacher is presented and the problems of transition from traditional to distance learning are identified. Some recommendations on health care in the distance learning format of mathematical disciplines are highlighted.